Awareness Of Eye Diseases and Satisfaction for Eye Care Services in Indore, India - Vaseem, Kausar; Baig, Vaseem Naheed; Rai, Puja; Swarnkar, Madhusudan (National Journal of Community Medicine, 2015)
Introduction: Objective of the study was to assess the knowledge of blinding eye diseases and the satisfaction for the eye services at government hospitals among community. Methods: This was a descriptive study 200 people of more than 18 years of age were given a close ended questionnaire. Their self re- ported responses were collected. Questions were related to their knowledge of eye disorders and their attitude toward eye related issues. Results: The knowledge about cataract was found to be good in more than 75% of respondents. 46% of the respondents were satis- fied with type of eye services provided in government hospitals. Difference of awareness between younger (<40 years) and older (>40 years) was found significant (P <0.05) for surgical treatment for cataract, younger children need examination and spectacle is necessary for refractive error in children. There was significant (P <0.05) difference found between males and females for knowledge about management of glaucoma, need of eye examination in younger children, continuous use of spectacle in children refractive error and treatment of squint. Conclusion: Awareness regarding the common eye diseases and their treatment and utilization of eye care facilities needs to be en- hanced for early detection and treatment thereby reducing the load of preventable blindness in our country.